Contribution of experimental fluid mechanics to the design of vertical slot fish passes - Wang R.W.; David L.; Larinier M. (Knowledge and Management of Aquatic Ecosystems, 2010)
This paper presents the main results of an experimental study of mean and turbulent characteristics of flow in a scale model of a vertical slot fish pass with varying width and slope (from 5% to 15%). Experimental hydraulic modelling was combined with the study of fish behaviour in the model. The discharge coefficient, which significantly affects the design of such facilities, varied from 0.67 to 0.89 and was strongly influenced by the slope. Two distinct flow patterns were observed, depending on the slope and the fish pass width. The point of transition between the two states was determined. Low velocity areas are likely resting zones for fish and particular attention was paid to evaluating these areas. Slope was found to affect both the volume of the low velocity zone, and the value of turbulent kinetic energy in these areas. The statistical characteristics of turbulent kinetic energy in the pools were linked primarily to the maximum velocity in the jet. An analysis of the behaviour of juvenile brown trout (Salmo trutta) in the scale model clearly showed that the fish avoided the areas of high velocities in the jet, except at the slot itself where they took advantage of the jet’s non-stationary character. Low-velocity areas were not frequented uniformly by fish, which stayed most frequently in the zone located just downstream from the slot and behind the small side baffle. It is suggested that future studies might investigate lower pool-length to slot-width ratios, which might make it possible to increase the slope significantly and should also examine ways of improving hydraulic conditions for fish by carefully distributing obstacles in pools.